QUALITY CONTROL OF WRITTEN BATIK CV. BATIK TULIS AL HUDA WITH STATISTICAL QUALITY CONTROL (SQC) METHOD - Handayani, Wiwik; Anhar, Hutama Muhammad; Murjana, Lilik (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
This study aims to analyze quality control at CV. Batik Tulis Al Huda. This type of research is quantitive descriptive research. In this research, the sample used was the number of the defect in the batik tulis product at CV. Batik Tulis Al Huda in 2019. This research uses the Statistical Quality Control method with tools namely check sheet, histogram, control chart, Pareto diagram, and cause-effect diagram. The results showed that the batik production process still experienced irregularities or was out of control. The overall level of damage reached 3.93% of the total production. Factors that cause defective products are human error, procedures that are not carried out properly, and equipment that is not in good condition.